2021
DOI: 10.1101/2021.03.08.21252819
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Plasma ACE2 levels predict outcome of COVID-19 in hospitalized patients

Abstract: Background Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) binds to angiotensin converting enzyme 2 (ACE2) enabling entrance of the virus into cells and causing the infection termed coronavirus disease of 2019 (COVID-19). COVID-19 is a disease with a very broad spectrum of clinical manifestations, ranging from asymptomatic and subclinical infection to severe hyperinflammatory syndrome and death. Methods This study used data from a large longitudinal study of 306 COVID-19 positive patients and 78 … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 40 publications
2
16
0
1
Order By: Relevance
“…Thus, several authors hypothesize that a down-modulation of ACE2 tissue activity-due to its shedding or internalization into the cells along with the virus-and the subsequent ACE/ACE2 imbalance could substantially contribute to the genesis of the hyperinflammatory state seen in COVID-19 [47,48]. However, it was demonstrated that sACE2 retains not only the capability of binding the virus, forming circulating sACE2-spike protein complexes, but also its enzymatic activity [45,52,53], and that in COVID-19 patients circulating ACE2 activity is actually increased, correlates positively with disease severity and remain elevated even after disease resolution [53,[118][119][120][121].…”
Section: Raas Dysfunction In Covid-19 Pathogenesismentioning
confidence: 99%
“…Thus, several authors hypothesize that a down-modulation of ACE2 tissue activity-due to its shedding or internalization into the cells along with the virus-and the subsequent ACE/ACE2 imbalance could substantially contribute to the genesis of the hyperinflammatory state seen in COVID-19 [47,48]. However, it was demonstrated that sACE2 retains not only the capability of binding the virus, forming circulating sACE2-spike protein complexes, but also its enzymatic activity [45,52,53], and that in COVID-19 patients circulating ACE2 activity is actually increased, correlates positively with disease severity and remain elevated even after disease resolution [53,[118][119][120][121].…”
Section: Raas Dysfunction In Covid-19 Pathogenesismentioning
confidence: 99%
“…Soluble ACE2 on the other side could re ect the cleavage of membrane-bound ACE2 by the SARS-CoV-2 entry and lysis of ACE2expressing cells. High levels of plasma ACE2 was proposed to indicate poor outcome in critically ill patients (19,20). The moderately affected disease process was different in our patients, in whom elevated ACE2 levels were seen in association with good outcomes without any ARDS, serious complication or mortality.…”
Section: Discussionmentioning
confidence: 53%
“…Compared to COVID − 19 patients without headache, serum levels of HMGB1, NLRP3, IL-6, angiotensin II, and ACE2 were signi cantly higher in COVID- 19 COVID-19 patients with headache and pulmonary in ltration (n = 31) had signi cantly higher serum levels of HMGB1, IL-6, D-dimer (Table-2). NLRP3 was correlated with headache duration (w = 0.69) and hospital stay (w = 0.63) in COVID-19 patients with headache (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…A confirmation that SARS-CoVs can induced an ACE2 hyperactivity comes from recent reports showing an increase of systemic ACE2 activity in COVID-19 patients and in accordance to disease severity ( Nagy et al, 2021 ; Patel et al, 2021 ; Reindl-Schwaighofer et al, 2021 ). Similarly, high circulating levels of sACE2 were significantly associated with worse or longer COVID-19 outcome in hospitalized patients ( Kragstrup et al, 2021 ; Lundström et al, 2021 ; Reindl-Schwaighofer et al, 2021 ). Notably, in healthy individuals circulating ACE2 activity is usually undetectable ( Lew et al, 2008 ), instead pre-existing high levels of circulating ACE2 protein/activity are typical of patients with comorbidities (e.g.…”
Section: Sars-cov-induced Ace2 (And Adam17) Zinc-metalloprotease Systemic Hyperactivity As a Possible Pathophysiological Origin Of Covid-mentioning
confidence: 90%
“…Notably, in healthy individuals circulating ACE2 activity is usually undetectable ( Lew et al, 2008 ), instead pre-existing high levels of circulating ACE2 protein/activity are typical of patients with comorbidities (e.g. male sex, age, cardiopathies, hypertension, diabetes) associated to severe COVID-19 (Anguiano et al, 2015; Epelman et al, 2009 ; Kornilov et al, 2020 ; Kragstrup et al, 2021 ; Narula et al, 2020 ; Ortiz-Pérez et al, 2013 ; Ramchand et al, 2018 ; Sama et al, 2020 ; Soro-Paavonen et al, 2012 ; Úri et al, 2014 , 2016 ; Wallentin et al, 2020 ; Walters et al, 2017 ), suggesting that an elevated baseline activity of ACE2 in circulation would predispose to severe COVID-19 because SARS-CoV infections would further increase ACE2 systemic activity. Altogether this evidence strongly supports the hypothesis that the main and initial cause of COVID-19 would be an excessive activity of circulating ACE2 zinc-metalloprotease, initially triggered by SARS-CoV infection ( Zamai, 2020a , 2021 ).…”
Section: Sars-cov-induced Ace2 (And Adam17) Zinc-metalloprotease Systemic Hyperactivity As a Possible Pathophysiological Origin Of Covid-mentioning
confidence: 99%